Partial detachment of high power discharges in ASDEX Upgrade. (22nd April 2015) - Kallenbach, A.; Bernert, M.; Beurskens, M.; Casali, L.; Dunne, M.; Eich, T.; Giannone, L.; Herrmann, A.; Maraschek, M.; Potzel, S.; Reimold, F.; Rohde, V.; et al.
Abstract: Detachment of high power discharges is obtained in ASDEX Upgrade by simultaneous feedback control of core radiation and divertor radiation or thermoelectric currents by the injection of radiating impurities. So far 2/3 of the ITER normalized heat flux P sep / R  = 15 MW m −1 has been obtained in ASDEX Upgrade under partially detached conditions with a peak target heat flux well below 10 MW m −2 . When the detachment is further pronounced towards lower peak heat flux at the target, substantial changes in edge localized mode (ELM) behaviour, density and radiation distribution occur. The time-averaged peak heat flux at both divertor targets can be reduced below 2 MW m −2, which offers an attractive DEMO divertor scenario with potential for simpler and cheaper technical solutions. Generally, pronounced detachment leads to a pedestal and core density rise by about 20–40%, moderate (<20%) confinement degradation and a reduction of ELM size. For AUG conditions, some operational challenges occur, like the density cut-off limit for X-2 electron cyclotron resonance heating, which is used for central tungsten control.